Perceraian Karena Pernikahan atas Kehamilan Diluar Nikah (Studi pada Kasus dengan Pola Asuh Permisif) - Happy Karlina Marjo (Jurnal Konseling dan Pendidikan, 2014)
The research was conducted to reveal the various facts about the permissive parenting parents against the impact of a single female parent’s teenager the end. Use case study in qualitative approach. On two of the respondents which of its characteristics are single parents teenager pregnant outside wedlock end then married in a short time and eventually divorced. Data were collected through interviews; observation and documentation study. Analyzed data qualitative descriptive usage through case studies and served in the form of narratives with earlier in Triangulation. Research results shows that the problem is becoming a single parent woman have an impact on the lives of young women as single parents. Respondents subjected to stress, standard of living is low a negative view of society and childcare; aspect role overload, poverty, loneliness and isolation, and felt to be a burden not affect the respondents. A family of permissive parenting causes the marriage is seen as a mere status only, so that after their child's birth status was not considered important, and they choose to become single parents. Further research showed the presence of moral deterioration and the difference in the impact of being a single parent on this research is influenced strongly by self resiliensi respondents. Counseling service to help explore the issues and deal with cases of teenagers as a single parent is indispensable.